The Onset and Prognosis of Hepatorenal Syndrome - Three Year Single Center Experience - Joksimovic, Nenad; Andreevski, Vladimir; Spasovski, Goce (BANTAO Association, 2010)
Introduction: The hepatorenal syndrome (HRS) refers to the development of acute renal failure in the setting of advanced liver disease. It can occur in a substantial proportion of patients with fulminate hepatic failure from any cause. The aim of our study was to investigate the onset, outcome and prognosis of patients with hepatorenal syndrome hospitalized at our unit. Methods: This is a cross-sectional retrospective study in a cohort of 543 cirrhotic patients, during a period of 3 years (January, 2008 - December, 2010). Hepatorenal syndrome was detected in 20 (3.7%) patients and in all of them a few variables such as: age, gender, history of cirrhosis or other liver disease, etiology of cirrhosis, Child-Pugh classification, other complications of the cirrhosis except for HRS, treatment and survival were analyzed. Results: The average preceding time up to the occurrence of HRS was around 3 years (36.8±47.8 months), although there were 4 patients who developed HRS only a month after the onset of cirrhotic symptoms. A group of seven patients with HRS diagnosed during the first year of the onset of symptoms. The mean age of patients was 55.5±13.3 years. There was a significant difference in the gender distribution, three quarters of patients being males. With regard to the etiology, 12 patients had alcoholic abuse, and a half of them (50%) were with mixed etiology (Hepatitis B plus alcohol abuse). Two patients had a pure chronic hepatitis B virus (HBV) infection as a cause of cirrhosis. Four were with chronic liver disease of unknown etiology (2 of them with confirmed histology of chronic hepatitis). All of the cirrhotic patients were scored as grade C according to the Child – Pugh classification. Hepatic encephalopathy was the most predominant concomitant complication present in 17 (85%) patients with HRS. Only 2 showed signs of malignancy with suspected hepatocellular carcinoma (HCC). The estimated average hospital stay was 6.15 days, ranging from 1-14 days. The applied treatment was generally unsuccessful. Majority of cases (14) were supported with albumin and fresh frozen plasma transfusion and haemodialysis was performed in 4 patients. The mortality rate was high, reaching 80% (16 patients) with an average time of death at 6.8±4.4 days after the hospital admission. Although the evaluation period was short, there is a clear raising trend in number of detected patients with HRS at our Clinical Center. Conclusion: Compared to other reports, our single centre experience shows lower occurrence rate. Despite the use of available conservative medical treatment, there was no recovery of the hepatic failure in any of HRS patients. The absence of liver transplantation or TIPS in our country is the second contributing factor related to the high mortality rate in our cohort. Finally, gastroenterohepatologists should be aware and try to prevent iatrogenic precipitants of HRS as an aggressive diuretic treatment or removal of large volumes of ascitic fluid by paracentesis without compensating for fluid depletion by intravenous replacement could additionally impair the renal failure.
Keywords: hepatorenal syndrome; hepatic failure; renal failure